Retention of small molecules on polymethacrylate monolithic capillary columns - Chocholoušková, Michaela; Komendová, Martina; Urban, Jiří (Journal of chromatography. A, Including electrophoresis and other separation methods, 2017)
In this paper, the concentration of N-isopropylacrylamide in the polymerization mixture has been varied to prepare several polymethacrylate monolithic capillary columns. Polymer monoliths combining N-isopropylacrylamide with zwitterion monomer, as well as various dimethacrylate crosslinking monomers have been prepared and characterized. Uracil, thiourea, phenol, toluene, ethylbenzene, propylbenzene, and butylbenzene have been used to characterize retention of prepared capillary columns in the mobile phases with 40-95% of acetonitrile and at working temperatures ranging from 25 to 60°C. By an optimization of six-parameter polynomial models we have found that the retention of small molecules is affected mainly by the concentration of the acetonitrile in the mobile phase with very low contribution of working temperature and combined effect of acetonitrile concentration and temperature. Concentration of the mobile phase controlled also enthalpy of the retention. On the other hand, entropic contribution was almost insensitive to the change of the mobile phase composition, especially for mobile phases containing more than 60% of acetonitrile.
Keywords: reprodukovatelnost výsledků; chromatografie; regresní analýza; Acrylamides; teplota; akrylamidy; Polymethacrylic Acids; kyseliny polymethakrylové; Entropy; Hydrodynamics; Reproducibility of Results; Temperature; Polymerization; Chromatography; entropie; polymerizace; hydrodynamika; Regression Analysis